The therapeutic potential of the insect metalloproteinase inhibitor against infections caused by Pseudomonas aeruginosa. (8th November 2018) - Eisenhardt, Michaela; Schlupp, Peggy; Höfer, Frank; Schmidts, Thomas; Hoffmann, Daniel; Czermak, Peter; Pöppel, Anne‐Kathrin; Vilcinskas, Andreas; Runkel, Frank
Abstract: Objectives: The objective of this study was to investigate the therapeutic potential of the insect metalloproteinase inhibitor (IMPI) from Galleria mellonella, the only known specific inhibitor of M4 metalloproteinases. Methods: The fusion protein IMPI‐GST (glutathione‐S‐transferase) was produced by fermentation in Escherichia coli and was tested for its ability to inhibit the proteolytic activity of the M4 metalloproteinases thermolysin and Pseudomonas elastase (PE), the latter a key virulence factor of the wound‐associated and antibiotic‐resistant pathogen Pseudomonas aeruginosa . We also tested the ability of IMPI to inhibit the secretome (Sec) of a P. aeruginosa strain obtained from a wound. Key findings: We found that IMPI‐GST inhibited thermolysin and PE in vitro and increased the viability of human keratinocytes exposed to Sec by inhibiting detachment caused by changes in cytoskeletal morphology. IMPI‐GST also improved the cell migration rate in an in vitro wound assay and reduced the severity of necrosis caused by Sec in an ex vivo porcine wound model. Conclusions: The inhibition of virulence factors is a novel therapeutic approach against antibiotic resistant bacteria. Our results indicate that IMPI is a promising drug candidate for the treatment of P. aeruginosa infections.